The genome sequence of the Bird-cherry Ermine moth, Yponomeuta evonymella (Linnaeus, 1758) [version 2; peer review: 2 approved, 1 approved with reservations] - Douglas Boyes; Callum Murray (Wellcome Open Research)
We present a genome assembly from an individual female Yponomeuta evonymella (the Bird-cherry Ermine; Arthropoda; Insecta; Lepidoptera; Yponomeutidae). The genome sequence has a total length of 572.70 megabases. Most of the assembly is scaffolded into 32 chromosomal pseudomolecules, including the trivalent sex chromosomes Z1, Z2 and W. The mitochondrial genome has also been assembled and is 16.16 kilobases in length.